Participation in SoHO and ATMP public consultations: a fragmented institutional landscape - Michael Morrison; Valentin Brunel; Aurélie Mahalatchimy (Humanities & Social Sciences Communications)
Abstract In the European Union (EU), the recent adoption of the Substances of Human Origin (SoHO) Regulation in June 2024 brings into force new harmonised rules for human cells, tissues and blood. This legislation interacts with the pre-existing Advanced Therapy Medicinal Products (ATMP) Regulation. This paper looks at the recent EU public consultations on the proposed SoHO Regulation and compares them with the prior consultations on the ATMP Regulation given the interplay between these two Acts. Information on each contributor to the three most recent consultations on SoHO and the two available consultations on the ATMP was collected, analysed, and used to develop a novel typology of entities participating in the consultations. This data set included the country of origin of each entity making a contribution and the type of entity involved (Academic/Research institutions, National Bodies, Companies, Business organizations, Patient and Consumer organizations, Learned Societies, Individual citizens, Networks/Innovation organizations, and Other Non-Governmental Organizations). The results show that the SoHO consultations attracted a far greater total volume of participants and displayed a greater variety of organizations from more distinct countries compared to the ATMP consultations. The most significant finding is the very low overlap in organisations making a contribution to both a SoHO and an ATMP consultations. This strongly suggests that there is significant institutional fragmentation between organisations collecting human biomaterials and organisations developing ATMP for market. Given that collection of biomaterials is a necessary first step in the development of most ATMP, European policy makers wishing to support ‘homegrown’ innovation with ATMP should give greater consideration to building better links between organisations collecting biomaterials and ATMP developers.